EFFECTIVENESS OF TRANSFORMATIVE LEARNING EXPERIENCES ON EMPLOYABILITY OF BACHELOR OF TECHNOLOGY PROGRAMME GRADUATES OF TECHNICAL UNIVERSITY OF KENYA - Ndeda, Gaudencia Achieng'; Wambiya, Paschal; Getui, Mary N. (African Journal of Education and Practice, 2020)
Purpose: This study sought to examine the effectiveness of transformative learning experiences on the employability of Bachelor of Technology Programme graduates of Technical University of Kenya. Methodology: The study used sequential explanatory design of the mixed method approach. Target population was 231 B. Tech graduates of the 2011, 2012 and 2013 cohorts all of which were included in the sample since they had limited numbers. Data were collected using a questionnaire and an interview guide. Reliability and validity index was calculated at between 0.8 and 0.9, an indication that the instruments were valid and reliable. The quantitative instrument was administered first and analysed, and the results used to construct the interview guide that was later conducted for explanatory purposes to validate the outcomes of the quantitative phase. The Perspective Transformation Index (PT-Index) on a scale of 1-3 was used. Responses were coded using Statistical Package for Social Sciences (SPSS) software for windows version 21.0 and presented using tables and figures. Findings: The majority (67.3%) of the B. Tech graduates experienced transformative learning. 71% of these attributed the transformation to the learning activities in the B.Tech programme (PT3) and16.3% to factors outside the B.Teh programme (PT2). Mentoring 85%, group project 58%, class presentation 46%, industry-based learning and trips 47%, class discussion and dialogue 47%, term papers and essays, self-evaluation, class activities and exercises, laboratory experiences and assigned readings all scored above 20%. Critical and creative thinking, and personal-self-reflection scored below 20%. New computers 37%, new technology support in the office 46%, new leadership13%, new professional requirements 43%, emerging unfamiliar work dimensions 16%, rapid transformation in Technology 45%, transformation in social life 27% and a feeling of incompetence 12%. Unique contribution: Theory: Transformative Learning can enhance employability of B.Tech graduates. Practice: The findings will inform design, implementation and improvement of academic curricula and training processes in institutions of higher learning. Policy: The findings can inform policy on transformative learning for greater employability.